PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP UNDANG-UNDANG NO. 5 TAHUN 2018 BAB VIIA TENTANG PENCEGAHAN TINDAK PIDANA TERORISME - Alika, Fitri; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Many cases of terrorism have occurred in Indonesia, one of which is according to the Coordinating Minister for Political, Legal and Security Affairs Mahfud MD, currently it is estimated that there are 660 Indonesian citizens who are members of foreign terrorist fighters or border crossing terrorists in various countries. The formulation of the problem in this study is how the perception of Riau University students towards Law No. 5 of 2018 Chapter VIIA on criminal acts of terrorism. The research objective was for the perception of Riau University students towards Law no. 5 of 2018 Chapter VIIA on the prevention of criminal terrorism. According to Law No. 5/2018 Criminal Acts of Terrorism are crimes committed with violence in a deliberate, systematic and planned manner, which creates an atmosphere of terror or widespread fear. This research method is descriptive quantitative, the data instruments used in this study are questionnaire, interviews and documentation. The population in this study were students of the University of Riau with a total population of 32.436 people. Sampling from the total population was taken using the Quota Sampling technique and to determine the respondents consisting of 20 expert researchers used the sampling technique. Based on the results of research and recapitulation that has been carried out by researcher respondents who answered Strongly agree (SS) + Agree (S) 30.13% + 47.94% = 78.07%. Thus it can be denied that the Perception of Riau University Students Against Law No. 5 of 2018 Chapter VIIA concerning the Prevention of Crime of Terrorism in the "Very Good" category where the Very Good range is in the range of 75.01% - 100%.Key Words: Student Perceptios,, Law No. 5 of 2018 Chapter VIIA